Overview of Protein and Fe Intake With The Event of Anemia In Adolescent: Systematic Review - Erningtyas, Cantika; Amalia, Rize Budi; Faizah, Zakiyatul (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2022)
Background: Adolescents are a group that is prone to anemia. Anemia is defined as a lower than normal haemoglobin level. The prevalence of anemia in adolescents in Indonesia is the highest at the age group of 15-24 years, 32%. The most common cause of anemia is lack of nutrients needed for erythrocyte synthesis. Substances that play a role in haemolysis are protein, vitamins (folic acid, vitamin B12, vitamin C and vitamin E), and minerals (Fe and Cu). Objective: To analyse the intake of protein and iron expected incidence of anemia in adolescent girls. Methods: This study used a systematic review method. The databases used to conduct this research are Scopus, PubMed, Science Direct, Portal Garuda and Google Scholar. The keywords used in Indonesian are